Uniaxial Stress Technique and Investigations of Correlated Electron Systems - Barber, Mark Edward (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2018)
This book reports on the development and application of a new uniaxial pressure apparatus that is currently generating considerable interest in the field of materials physics. The author provides practical guidelines for performing related experiments, backed up by finite element simulations. Subsequently, the book reports on two uses of the device. In the first, high pressures are used to tune to a Van Hove singularity in Sr2RuO4, while the effects on the unconventional superconductivity and the normal state properties are investigated. In the second experiment, precise and continuous strain control is used to probe symmetry breaking and novel phase formation in the vicinity of a quantum critical point in Sr3Ru2O7. .